Resilience and social support of young adults living with mental illness in the city of Tshwane, Gauteng province, South Africa - Nok'khanya F. Hadebe; Tendani S. Ramukumba (AOSIS, 2020)
Background: Young adults living with mental illnesses often experience a flood of powerful negative emotions, including anger, anxiety, and depression. Some of these young adults remain trapped in those negative emotions long after the stressful events that caused them have passed, while resilient young adults without mental illness are able to quickly bounce back to their normal emotional state. Objectives: The objective of the study was to explore social support of young adults living with mental illnesses in the City of Tshwane. Methods: This was a qualitative explorative study done in the City of Tshwane in 2018 among young adults living with mental illnesses, using a semi-structured interview schedule. Results: Those young adults living with mental illness who had support from family and friends were able to cope with stressful challenges and had a better outlook for the future, while those who perceived their relationship with friends and family as not supportive reported low self-esteem and difficulties dealing with challenging and stressful situations in their lives. Conclusion: Resilience was seen in those young people living with mental illness with support from family and friends, who had positive future prospects, those with high self-esteem, and those who were able to adapt to changing situations beyond their control.